2016
DOI: 10.1049/iet-syb.2015.0066
|View full text |Cite
|
Sign up to set email alerts
|

Increased inflammation in sanctuary sites may explain viral blips in HIV infection

Abstract: Combined antiretroviral therapy (cART) is a powerful therapy to suppress HIV-1 viral replication. Although in treatment, viral load in plasma remains below the limit of detection in regular assays, 50copiesmL, intermittent episodes of transient viremia (viral blips) over the limit of detection occur in a significant set of HIV-patients under cART. Here, we develop a model-based study of a possible relation between ongoing replication in lymphoid-tissue-based sanctuary sites and viral blips. Given that follicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The higher serum IL10 level in sepsis compared to all other ICU pathologies may suggest that EBV and CMV reactivation could be triggered by molecular events mediated by stress, local trauma, or unrelated infections ( 45 , 46 ), rather than associated with pre-existing immune suppression ( 11 , 45 , 47 ). Alternatively, we observed low-level viraemia or viral “blips” for herpesviruses rather than significant viral rebound; hence, reactivation may result from increased inflammation in sanctuary sites or reservoirs as described in HIV infection ( 48 , 49 ) or to immunosurveillance activities of neighbouring cells ( 50 ). The changes observed in TTV viraemia in ICU patients in this study indicate the need for further exploration of the process of reactivation/modulation of expression of TTV.…”
Section: Discussionmentioning
confidence: 76%
“…The higher serum IL10 level in sepsis compared to all other ICU pathologies may suggest that EBV and CMV reactivation could be triggered by molecular events mediated by stress, local trauma, or unrelated infections ( 45 , 46 ), rather than associated with pre-existing immune suppression ( 11 , 45 , 47 ). Alternatively, we observed low-level viraemia or viral “blips” for herpesviruses rather than significant viral rebound; hence, reactivation may result from increased inflammation in sanctuary sites or reservoirs as described in HIV infection ( 48 , 49 ) or to immunosurveillance activities of neighbouring cells ( 50 ). The changes observed in TTV viraemia in ICU patients in this study indicate the need for further exploration of the process of reactivation/modulation of expression of TTV.…”
Section: Discussionmentioning
confidence: 76%
“…First, there is evidence for residual viral replication due to the low concentrations of antiretroviral drugs in sanctuary sites are present throughout the body, including the lymph nodes, central nervous system, tissue macrophages, adipose tissue, and the gut-associated lymphoid tissue [65][66][67][68][69][70]. It has also been reported that temporal elevation of viral production, "viral blip", is induced by transient inflammation in the sanctuary sites [71,72]. In our study, the proportion of viral blips in the Vpr-positive patients was negligible both in the tumor group (5.2%, 6 of 115 patients) and the non-tumor group (6.1%, 4 of 66 patients) (Table 3) and none of factors including HIV viremia were predicted with Vpr emergence status (S3 Table ), further implying that the production of Vpr was not due to the viral blip.…”
Section: Plos Onementioning
confidence: 99%
“…3 ), using infection dynamic rates and tissue transport rates derived from a number of human and animal studies. Analyzing this model leads to several interesting insights [ 55 , 56 ]. The model demonstrates that a lower limit in sanctuary size is necessary to sustain ongoing replication, even when no antiretrovirals are present.…”
Section: Mathematical Modeling Of Episomal Hiv Dnamentioning
confidence: 99%